Potential implementation strategies, acceptability, and feasibility of new and repurposed TB vaccines - Puck T. Pelzer; Janet Seeley; Fiona Yueqian Sun; Michele Tameris; Li Tao; Zhao Yanlin; Hisham Moosan; Chathika Weerasuriya; Miqdad Asaria; Sahan Jayawardana; Richard G. White; Rebecca C. Harris (PLOS Global Public Health, 2022)
Recently, two Phase 2B tuberculosis vaccine trials reported positive efficacy results in adolescents and adults. However, experience in vaccinating these age groups is limited. We identified potential implementation strategies for the M72/AS01E vaccination and BCG-revaccination-like candidates and explored their acceptability and feasibility. We conducted in-depth semi-structured interviews among key decision makers to identify implementation strategies and target groups in South Africa, India, and China. Thematic and deductive analysis using a coding framework were used to identify themes across and within settings. In all three countries there was interest in novel TB vaccines, with school-attending adolescents named as a likely target group. In China and India, older people were also identified as a target group. Routine vaccination was preferred in all countries due to stigma and logistical issues with targeted mass campaigns. Perceived benefits for implementation of M72/AS01E were the likely efficacy in individuals with Mycobacterium tuberculosis (Mtb) infection and efficacy for people living with HIV. Perceived challenges for M72/AS01E included the infrastructure and the two-dose regimen required. Stakeholders valued the familiarity of BCG but were concerned about the adverse effects in people living with HIV, a particular concern in South Africa. Implementation challenges and opportunities were identified in all three countries. Our study provides crucial information for implementing novel TB vaccines in specific target groups and on country specific acceptability and feasibility. Key groups for vaccine implementation in these settings were identified, and should be included in clinical trials and implementation planning.